The abandoned women in Sindiwe Magona's writing - Matlala, Everlyn R. C. (My University, 2003)
Refer to the document
Thesis (M. A. (English Studies)) -- University of Limpopo, 2003
Keywords: Women in literature; Women abuse; Abandonment of women; Abused women